CLIL AS A METHOD IN TEACHING SPORT COLLEGE STUDENTS THROUGH BILINGUAL CLASS PROGRAM - Limpad Nurrachmad (Prominent, 2019)
The internationalization of institutions proclaimed by Universitas Negeri Semarang has led to the emergence of bilingual class program in every study program. The challenge faced when there are bilingual classes is the ability of lecturers in several majors to provide courses in both English and Bahasa. This study aims at answering the challenges currently faced by UNNES when providing a bilingual class. Then, it is to illustrate and describe the implementation of Content and Language Integrated Learning (CLIL) on the tennis class at the Faculty of Sport Science. The result show that combination of CLIL and SFL was chosen because CLIL teaching method has two simultaneous focuses on content and language while SFL is a teaching method emphasizing the deconstruction of academic genres texts as well as explicit teaching on text features. It is expected that the combination of the two can produce teaching methods that emphasize course material and mastery of English as a medium of instruction in a balance and easier to understand due to the explicit deconstruction of academic texts.